2013
DOI: 10.1371/journal.pone.0063608
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Inotropic Effect of Pyruvate Involves an Increase in Myofilament Calcium Sensitivity

Abstract: Pyruvate is a metabolic fuel that is a potent inotropic agent. Despite its unique inotropic and antioxidant properties, the molecular mechanism of its inotropic mechanism is still largely unknown. To examine the inotropic effect of pyruvate in parallel with intracellular calcium handling under near physiological conditions, we measured pH, myofilament calcium sensitivity, developed force, and calcium transients in ultra thin rabbit heart trabeculae at 37 °C loaded iontophoretically with the calcium indicator b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 49 publications
(73 reference statements)
5
18
0
Order By: Relevance
“…2a) is in accordance to the tendency found in other reports (Kerr et al 1999;Diolez et al 2007). However, some studies found that Pyr is a positive inotropic agent in several species, e.g., rabbit and human (Leite-Moreira et al 2002;Keweloh et al 2007;Torres et al 2013), dog (Mentzer et al 1989;Yanos et al 1994), guinea-pig (Daut and Elzinga 1989), and rat (Martin et al 1998), while others did not find any inotropic change in rat hearts (Ojha et al 2012). This difference in behavior can be attributed to several factors, such as in vivo vs. in vitro experiments, temperature, and concentration.…”
Section: Effects Of Pyr In Pre-ischemic Perfused Ventriclessupporting
confidence: 87%
See 1 more Smart Citation
“…2a) is in accordance to the tendency found in other reports (Kerr et al 1999;Diolez et al 2007). However, some studies found that Pyr is a positive inotropic agent in several species, e.g., rabbit and human (Leite-Moreira et al 2002;Keweloh et al 2007;Torres et al 2013), dog (Mentzer et al 1989;Yanos et al 1994), guinea-pig (Daut and Elzinga 1989), and rat (Martin et al 1998), while others did not find any inotropic change in rat hearts (Ojha et al 2012). This difference in behavior can be attributed to several factors, such as in vivo vs. in vitro experiments, temperature, and concentration.…”
Section: Effects Of Pyr In Pre-ischemic Perfused Ventriclessupporting
confidence: 87%
“…The temperature-dependence of Pyr effect may be the result of a balance among its several cellular effects. At a physiological temperature, the positive inotropism of Pyr suggests the predominance of mechanisms activated by the rise in aerobic metabolism, such as phosphorylation potential, SR Ca 2+ store, and myofilament Ca 2+ sensitivity (Zima et al 2003;Mallet et al 2005;Torres et al 2013). They would be exceeding the negative Fig.…”
Section: Effects Of Pyr In Pre-ischemic Perfused Ventriclesmentioning
confidence: 99%
“…Even though fura 4F has not yet been used in optical mapping experiments, sophisticated multiparametric optical mapping systems are being developed for ratiometric imaging of both high-and low-affinity Ca 2ϩ probes (36,56). Future studies of myocardial metabolism, where changes in Ca i 2ϩ , mitochondrial redox state, and mitochondrial membrane potential are measured (2,39,91,98), would certainly benefit from accurate measurements of relative changes in Ca i 2ϩ using ratiometry. Quantification of nonratiometric signals.…”
Section: Ca I 2ϩ Fluorescence Probesmentioning
confidence: 99%
“…Ca i 2ϩ dynamics and metabolism. In metabolic studies, changes in Ca i 2ϩ kinetics that alter contractile function in perfused hearts are measured using Ca 2ϩ fluorescence probes (14,39,98). For example, paired optical mapping studies that measured developed pressure, NADH fluorescence, and Ca i 2ϩ transients in perfused rat hearts provided mechanistic insights into the inotropic effects of pyruvate and dichloroacetate, two compounds that promote full glucose oxidation in myocytes (39).…”
Section: Investigations Of Physiology and Diseasementioning
confidence: 99%
“…Administering pyruvate would not correct an imbalance between glycolysis and full glucose oxidation: in fact, any imbalance would be exacerbated. Numerous other studies have investigated the mechanisms by which pyruvate improves cardiac function without the confounding variable of ischemia [10, 46, 52]; however, there are very few investigations of the mechanisms of DCA in the absence of ischemia.…”
Section: Introductionmentioning
confidence: 99%